Incidence of Dysmagnesemia among Medically Hospitalized Patients and Associated Clinical Characteristics: A Prospective Cohort Study - Zahra Al Shukri; Juhaina Salim Al-Maqbali; Abdullah M. Al Alawi; Nafila Al Riyami; Sulaiman Al Riyami; Hiba Al Alawi; Qatiba Al Farai; Henrik Falhammar (International Journal of Endocrinology)
Background. Magnesium (Mg) disorders are common among hospitalized patients and are linked to poor health outcomes. We aimed to determine the incidence of dysmagnesemia among medically hospitalized patients and to identify factors that are associated with dysmagnesemia. Methods. A prospective cohort study was conducted at Sultan Qaboos University Hospital (SQUH) from April 1st, 2022, to October 31st, 2022, and involved hospitalized adult patients (≥18 years) under the care of the general internal medicine unit. The patients’ serum total magnesium (Mg) concentrations were categorized as hypomagnesemia (≤0.69 mmol/L), hypermagnesemia (≥1.01 mmol/L), or dysmagnesemia, which encompassed either hypomagnesemia or hypermagnesemia. Results. Of the 304 patients evaluated, dysmagnesemia was observed in 22.0%, which comprised of 17.4% with hypomagnesemia and 4.6% with hypermagnesemia. Statistically significant associations were identified between hypermagnesemia and chronic kidney disease (CKD) (p = 0.05) and elevated creatinine levels (p < 0.01) and lower estimated glomerular filtration rate (eGFR) (p < 0.01). Hypomagnesemia was linked to lower ionized calcium (p = 0.03) and admission due to infectious diseases (p = 0.02). However, ordered regression analysis did not find any significant associations with the different magnesium groups. Conclusion. Dysmagnesemia was prevalent among hospitalized patients and was associated with different factors; however, ordered regression analysis did not find any association with the different magnesium group, probably due to the limited number of included individuals.